Azocarboxamide-enabled enantioselective regiodivergent unsymmetrical 1,2-diaminations - Yun-Dong Fu; Han Zhang; Bei-Bei Li; Lihua Huang; Xiao Xiao; Min-Can Wang; Donghui Wei; Guang-Jian Mei (Nature Communications)
Abstract Enantioenriched unsymmetrical vicinal diamines are important basic structural motifs. While catalytic asymmetric intermolecular 1,2-diamination of carbon–carbon double bonds represents the most straightforward approach for preparing enantioenriched vicinal-diamine-containing heterocycles, these reactions are often limited to the installation of undifferentiated amino functionalities through metal catalysis and/or the use of stoichiometric amounts of oxidants. Here, we report organocatalytic enantioselective unsymmetrical 1,2-diaminations based on the rational design of a bifunctional 1,2-diamination reagent, namely, azocarboxamides (ACAs). Under the catalysis of chiral phosphoric acid, unsymmetrical 1,2-diaminations of ACAs with various electron-rich double bonds readily occur in a regiodivergent manner. Indoles prefer dual hydrogen-bonding mode to give dearomative (4 + 2) products, and 3-vinylindoles and azlactones are inclined to undergo unsymmetrical 1,2-diamination via the (3 + 2) process. DFT calculations are performed to reveal the reaction mechanism and the origin of the regio- and enantioselectivity. Guided by computational design, we are able to reverse the regioselectivity of the dearomative unsymmetrical 1,2-diamination of indoles using Lewis acid catalysis.